The Effect of Breakfast Skipping and Late Night Eating on Body Mass Index and Glycemic Control Among Patients With Type 2 Diabetes Mellitus - Mirghani, Hyder (Cureus, 2021)
Introduction There is an increasing awareness regarding the effects of chrono-nutrition on glycemic control and weight regulation. Therefore, this study aimed to determine the relationship between breakfast skipping and late-night eating to body mass index and glycemic control among patients with type 2 diabetes. Subjects and methods This cross-sectional study was conducted among 310 patients with diabetes in Tabuk City, Saudi Arabia during the period from December 2020 to April 2021. A structured questionnaire was used to interview the participants, the following were reported: demographic data, breakfast skipping, late-night eating, smoking, level of exercise, family history of diabetes, and diabetes complications. Weight and height were measured to calculate the body mass index (BMI), and the last glycated hemoglobin was collected to estimate the degree of glycemic control. Statistical Package for Social Sciences (SPSS Statistics, IBM Corp., Armonk, USA) was used for data analysis. The ethical committee of the University of Tabuk approved the research. Results Out of 310 patients with diabetes (54.8% women), nearly half (45.2%) were breakfast-skippers and 20% eat late at night. Breakfast skipping was correlated with BMI (Wald, 5.481, 95% CI, 0.154-0.847, P-value, 0.019). A positive direct correlation was evident between late dinner intake, BMI, and HbA1c (Wald, 4.210, 95% CI, 0.743-0.993, P-value, 0.04 for HbA1c, and Wald, 6.777, 95% CI, 1.0221-1.165, P-value, 0.009 for BMI). Conclusion Breakfast skipping and late dinner intake were associated with obesity, while only late dinner consumption was associated with poor glycemic control. Further larger multi-center studies investigating the chronotype and glycemic index are recommended.